Study on bending fatigue failure behaviors of end-fixed wire ropes. (May 2022) - Hu, Zhen; Wang, Enyuan; Jia, Fuyin
Highlights: A wire rope bending fatigue testing machine by which torsion fatigue is considered innovatively was introduced. The rope damage evolution was tracked by means of manual detection and non-destructive testing. The fracture and wear marks of steel wires were observed by optical microscope, the damage mechanism was investigated. Abstract: Torsional fatigue always exists after a wire rope is put into use, which results in damage aggravation and lifespan reduction. This study is aimed at exploring the comprehensive tribo-fatigue behaviors of wire rope considering torsional fatigue. To achieve this aim, a new type of self-made fatigue testing machine was introduced, and the bending fatigue tests were carried out. Furthermore, the diameter shrinkage ratio, the number and distribution of broken wires under different fatigue times were studied by means of manual detection and non-destructive testing. Moreover, the fractures and wear scars were investigated with the aid of the LW200-4JT optical microscope system. For the thicker outer wire of spiral strand (SS), the influences of bending fatigue times on the evolution of wear parameters were comparatively analyzed. The research results are as follows. With the increase of bending fatigue times, the diameter shrinkage ratio increases, and the increase decelerates gradually. The artificial statistical results agree well with the non-destructive testing results. To be specific, the broken wire develops slowly in the early stage of fatigue, whereas it develops rapidly when the fatigue times exceed 60, 000. The broken wire is highly concentrated in the thicker outer wire of SS 1. The maximum width and depth of wear scars of the thicker outer wire of SS 1 increase with the increase of cycles. The values of the two parameters at different contact positions follow the order: contact with the pulley > contact with the adjacent SS 1 > contact with the SS 2 > contact with the wire in the adjacent layer in the same strand. This study is expected to find the fatigue failure rules of end-fixed hoisting wire rope, thus providing a basis for improving the safety of mine hoisting.